Respostas
respondido por:
2
.
Ola Anagabriela
6x/5 = (-5 - y)/4
2*(x + 2) = 3*(y - 6)
24x + 5y + 25 = 0
2x + 4 = 3y - 18
2x - 3y + 22 = 0
sistema
24x + 5y = -25
2x - 3y = -22
72x + 15y = -75
10x - 15y = -110
82x = -185
x = -185/82
-185/41 - 3y = -22
3y = -185/41 + 22*41/41
3y = -185/41 + 902/41 = 717/41
y = 239/41
.
Ola Anagabriela
6x/5 = (-5 - y)/4
2*(x + 2) = 3*(y - 6)
24x + 5y + 25 = 0
2x + 4 = 3y - 18
2x - 3y + 22 = 0
sistema
24x + 5y = -25
2x - 3y = -22
72x + 15y = -75
10x - 15y = -110
82x = -185
x = -185/82
-185/41 - 3y = -22
3y = -185/41 + 22*41/41
3y = -185/41 + 902/41 = 717/41
y = 239/41
.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás